An Overview of the Available Intervention Strategies for Postural Balance Control in Individuals with Autism Spectrum Disorder. (21st November 2022) - Hariri, Rabeeh; Nakhostin-Ansari, Amin; Mohammadi, Fatemeh; Memari, Amir Hossein; Oskouie, Iman Menbari; Haghparast, Afarin
Abstract : Background . Postural instability is a prevalent issue among individuals with autism spectrum disorder (ASD) that affects the development of their perceptual-motor skills and social functioning. Visual and somatosensory processing deficits, hypotonia, basal ganglia dysfunction, and anxiety are some of the concurrent disorders in individuals with ASD. Nevertheless, a definite management protocol for postural instability in ASD has not been introduced yet. Hence, we aim to shed light on the available intervention strategies for postural instability in individuals with ASD. Methods . Even though several studies have been conducted on the effects of various interventions for balance control in individuals with ASD, no study has compared their efficacy, limitations, and clinical implications. Results . This review discusses diverse proposed interventions contributing to ASD postural instability, including martial arts, water-based interventions, animal-assisted therapies, trampoline, balance training, vestibular therapy, transcranial direct current stimulation, sports, play, and active recreation for kids (SPARK), and square-stepping exercise (SSE). Conclusion . Enhancing motor skills, cerebellum function, and sensory input integration were some of the main mechanisms of these interventions to improve balance control in ASD. Some interventions, such as water-based exercises and video games, were enjoyable for children with ASD and could raise their treatment adherence. In most studies, small sample sizes and the lack of a control group represented their major limitations. Therefore, future well-designed randomized controlled trials are required to assess the effects of available interventions on postural control in ASD.